Long-term effects of continuous direct seeding mulch-based cropping systems on soil nitrogen supply in the Cerrado region of Brazil - Maltas, A; Corbeels, Marc; Scopel, E.; Oliver, R.; Douzet, Jean-Marie; Silva, F.A.M. da; Wery, Jacques (Springer, 2007)
In the Cerrado region of Brazil conventional soybean monoculture is since the 1980s being replaced by direct seeding mulch-based cropping (DMC) with two crops per year and absence of tillage practices. The objective of this study was to assess the long-term impact of DMC on soil organic matter accumulation and nitrogen (N) mineralization. Measurements of soil organic carbon (C) content, soil total N content and soil N mineralization, both under laboratory conditions using disturbed soil samples and under field conditions using intact soil cores were conducted on a chronosequence of 2-, 6-, 9- and 14-year-old DMC fields (DMC-2, DMC-6, DMC-9 and DMC-14, respectively). The average increase of organic C in the 0–30 cm topsoil layer under DMC was 1.91 Mg C ha?1 year?1. Soil total N increased with 103 kg N ha?1 year?1 (0–30 cm). The potential N mineralization rate under laboratory conditions (28°C, 75% of soil moisture at field capacity) was 0.27, 0.28, 0.39 and 0.36 mg N kg soil?1 day?1 for, respectively, the DMC-2, DMC-6, DMC-9 and DMC-14 soils. The corresponding specific N mineralization rates were 0.16, 0.15, 0.22 and 0.17 mg N g N?1 day?1. There was no obvious explanation for the higher specific N mineralization rate of soils under DMC-9, given the similar soil conditions and land-use history before DMC was introduced. Results from the in situ N incubation experiments were in good agreement with those from the laboratory incubations. We estimated that soil N mineralization increases with about 2.0 kg N ha?1 year?1 under DMC. The increase was mainly attributed to the larger soil total N content. These results indicate that even in the medium term (10 years), continuous DMC cropping has limited implications for N fertilization recommendations, since the extra soil N supply represents less than 20% of the common N fertilization dose for maize in the region.